A 30-day risk assessment of mastectomy alone compared to immediate breast reconstruction (IBR). Issue 3 (June 2014) - Fischer, John P.; Tuggle, Charles T.; Au, Alex; Kovach, Stephen J.
Abstract Immediate breast reconstruction (IBR) is emerging as a favourable reconstruction option for breast cancer patients. Understanding the factors associated with complications following IBR will enhance care delivery, risk counselling and management, and potentially improve patient satisfaction. Women undergoing mastectomy alone and mastectomy with IBR from 2005–2011 were identified in the ACS-NSQIP datasets. Specific complications examined included surgical (flap or prosthesis loss and unplanned reoperation), wound (superficial/deep surgical site infection and wound dehiscence), and medical complications. Bivariate and multivariate analyses were performed to identify predictors of outcomes. A total of 47, 443 patients were identified. For patients who underwent IBR compared to mastectomy alone, total complications (11.2% vs 9.2%, p < 0.001) and surgical complications (7.8% vs 4.7%, p < 0.001) were more frequent. In adjusted analysis, a common predictor of complications was class III obesity (BMI ≥ 40 kg/m2) for mastectomy alone (OR = 1.79, p < 0.001) and implant-based IBR (OR = 2.20, p < 0.001), and class II obesity (BMI 35–39.9) for autologous IBR (OR = 1.62, p = 0.003). Wound complications were found to be associated with autologous reconstruction (p < 0.001 kg/m2), smoking (p < 0.001), bilateral procedures (p = 0.005), patient comorbidity (p = 0.006), obesity (p < 0.001), and diabetes (p < 0.001). The strongest predictors of wound complications were class II obesity (OR = 2.12), class III obesity (OR = 3.09), and smoking (OR = 1.70). Risk factors for medical morbidity included: immediate autologous (p < 0.001), recent chemotherapy (p = 0.013), ASA physical status (p < 0.001), bilateral procedure (p = 0.002), patient comorbidity (p < 0.001), and obesity (p < 0.001). The strongest predictors of medical morbidity were immediate autologous reconstruction (OR = 3.54) and comorbidity burden of ≥2 comorbid conditions (OR = 2.28). In conclusion, undergoing IBR is associated with a modality-specific increased risk of morbidity relative to mastectomy alone. However, other modifiable risk factors appear to be strongly correlated with postoperative complications. Level of Evidence: prognostic/risk category, level II.